ISLAM DAN PENDIDIKAN MULTIKULTURALISME - Hidayati, Inayah (Pascasarjana IAIN Kudus, 2013)
The education institution has the big role to influence the implementation of multiculturalism in this country. First, It is startedfrom the university which is the highest level of education. Theuniversity institution can apply and conduct the multiculturalismeducation by organising and developing the concept ofmulticultural, e.g. the study centre of Islam for non-moslems, thecolaboration between Islamic University and state university,morever non-islamic university. Second, The school instution alsohas the influential role in developing the multicultural education.There are two prime component, first is the teacher. The teacherhold the urgent role in implementing the multicultural value fortheir students. It is supposed that the teacher has the paradigma ofdiversity understanding, so they are able to teach their students bygiving the argument democrately towards the world multiculturalissues or conflicts which occured. The islam education based on themulticulticultural material can be developed and applied in somelearning subjects. Finally, there will be the balance between Islam and multicultural and the conflicts can be minimized.